An exploration of the role of short term medical missions in health care provision in Honduras : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University, Turitea, Palmerston North, New Zealand - McLennan, Sharon Joy; McLennan, Sharon Joy (Massey University, 2005)
Short term medical missions, or medical brigades are teams of expatriate health professionals and lay people, who travel to Latin America and other parts of the world for a week or two to provide health care to the poor. While the number and popularity of these teams appears to be increasing, to date there has been little literature or critical research addressing their role. This thesis addresses the role of Short Term Medical Missions (STMMs), who they are, what they do and how they fit into health service provision in developing nations. In particular it outlines the services provided by STMMs, including clinical services, resource provision and preventative services, it discusses the motivation for using STMMs as service providers and it also begins to explore the impact they have on the populations and on local health care services in the areas they operate. This is done within the context of Honduras, a nation that has seen an influx of these teams in recent years, particularly since Hurricane Mitch in 1998. Honduras faces many challenges in health and health care and STMMs have been seen by some as a means of “filling gaps”. This study questions whether STMMs are indeed actually filling real gaps, and if they are, whether they most appropriate means of doing so, as there are many limitations to the ability of short term, outside volunteers to provide quality services. While not directly measuring the impact of STMMs on the health status of the population, this study discusses the actual and potential impact of STMMs on local health services, and argues that there are potential long-term consequences to their use. These consequences include an increasing dependency on outside assistance that may be detrimental to the long-term development of National health services.
Keywords: Health services; Health care; Latin American health care